2018
DOI: 10.1016/j.celrep.2018.04.073
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Entorhinal Cortical Projections to the Dentate Gyrus Underlies Social Memory Retrieval

Abstract: Social interactions are essential to our mental health, and a deficit in social interactions is a hallmark characteristic of numerous brain disorders. Various subregions within the medial temporal lobe have been implicated in social memory, but the underlying mechanisms that tune these neural circuits remain unclear. Here, we demonstrate that optical activation of excitatory entorhinal cortical perforant projections to the dentate gyrus (EC-DG) is necessary and sufficient for social memory retrieval. We furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 50 publications
4
46
0
3
Order By: Relevance
“…There are some reports showing that adult-born neurons are important for spatial memory acquisition and retrieval (Gu et al, 2012;Tronel et al, 2015), yet less is known about adult-born neurons and memory maintenance/consolidation. While the dentate gyrus itself has been shown to be important for social memory retrieval (Leung et al, 2018), the link between this brain region and social memory maintenance has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports showing that adult-born neurons are important for spatial memory acquisition and retrieval (Gu et al, 2012;Tronel et al, 2015), yet less is known about adult-born neurons and memory maintenance/consolidation. While the dentate gyrus itself has been shown to be important for social memory retrieval (Leung et al, 2018), the link between this brain region and social memory maintenance has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical information largely enters the hippocampus via the perforant pathway from the entorhinal cortex which forms synapses onto the DG, CA3 and CA2 regions . Optogenetic inhibition of entorhinal inputs in the dorsal DG does not impact sociability but impairs social recognition in mice, implicating the EC‐DG synapse as an important component for social memory. However, another recent study shows that the deletion of the n ‐methyl‐ d ‐aspartate receptor (NMDAR) NR1 subunit from the DG granule cells—effectively eliminating NMDAR‐dependent plasticity—does not produce deficits in social memory of male mice .…”
Section: Oxytocin and Vasopressin Modulation Of Hippocampal‐dependentmentioning
confidence: 99%
“…58 Chemogenetic silencing of dorsal CA2 inputs to the ventral CA1 via local infusions of clozapine-n-oxide robustly impairs social memory, 99 further supporting a dorsal CA2 to ventral CA1 circuit underlying social memory. The CA1 also receives monosynaptic input from the EC, however, optical inhibition of this pathway in the ventral CA1 region does not impair social recognition, 92 suggesting information transfer from the CA2/CA3 region is more important for this task. Additionally, stimulation or inhibition of inputs from the basolateral amygdala to the ventral CA1 region of male mice bidirectionally influences social behavior.…”
Section: The Hippocampus and Social Memorymentioning
confidence: 99%
“…The lack of discrimination between social targets in the social novelty test may indicate impairment in social memory 47 . It has been shown that hippocampal neurons mediate social memory 48 , and that neurons projecting from the cortex to the hippocampus can affect social memory without affecting sociability 49 . Understanding the differences in these models requires further study.…”
Section: Discussionmentioning
confidence: 99%